Long-term ex vivo maintenance of testis tissues producing fertile sperm in a microfluidic device - Komeya, Mitsuru (Sci Rep, 2016)
In contrast to cell cultures, particularly to cell lines, tissues or organs removed from the body cannot be maintained for long in any culture conditions. Although it is apparent that in vivo regional homeostasis is facilitated by the microvascular system, mimicking such a system ex vivo is difficult and has not been proved effective. Using the culture system of mouse spermatogenesis, we addressed this issue and devised a simple microfluidic device in which a porous membrane separates a tissue from the flowing medium, conceptually imitating the in vivo relationship between the microvascular flow and surrounding tissue. Testis tissues cultured in this device successfully maintained spermatogenesis for 6 months. The produced sperm were functional to generate healthy offspring with micro-insemination. In addition, the tissue kept producing testosterone and responded to stimulation by luteinizing hormone. These data suggest that the microfluidic device successfully created in vivo-like conditions, in which testis tissue maintained its physiologic functions and homeostasis. The present model of the device, therefore, would provide a valuable foundation of future improvement of culture conditions for various tissues and organs, and revolutionize the organ culture method as a whole.